The Effectiveness of Digital Media in Improving Learning Outcomes in Islamic Religious Education Among High School Students in Padangsidimpuan City - Sulham Efendi Hasibuan; Efridawati Harahap; Eva Juliana; Saqdiatul Khoiriyah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2026)
This study aims to analyze the effectiveness of digital media use in improving Islamic Religious Education (PAI) learning outcomes for high school students in Padangsidimpuan City. The background of this study is based on the increasingly rapid development of digital technology and has had a significant impact on the world of education, including in the PAI learning process. Digital media such as learning videos, e-learning platforms, interactive applications, and multimedia-based presentations are considered capable of creating a more interesting and interactive learning process, and making it easier for students to understand abstract material. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to high school students in Padangsidimpuan City who have used digital media in PAI learning. Data analysis was carried out using descriptive and inferential statistics to determine the level of effectiveness and influence of digital media use on student learning outcomes. The results of the study indicate that the use of digital media in PAI learning is in the good and effective category in improving student learning outcomes. This is indicated by an increase in understanding of religious concepts, learning motivation, and student involvement in the learning process. In addition, there is a positive and significant influence between the use of digital media on students' PAI learning outcomes. Thus, it can be concluded that digital media is an effective learning innovation in improving the quality of Islamic Religious Education learning outcomes in high schools in Padangsidimpuan City.